(3TQM bhGYO YjGVs - (3CMeO Hf jhSa GdHQdSi GdeGdcjs; (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s
(3ChdgG (B:s
(3hHO agPG eNJUQ ai TQM cJH bhGYO YjGV s
(3BNQgG (B:s
(3heGPfHi Shi Effi ZQjH s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B16s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B243s
Keywords: (3CUhd Gdabgs